Screening for distress, the sixth vital sign: examining self‐referral in people with cancer over a one‐year period. Issue 2 (2nd December 2011) - Waller, Amy; Williams, Andrea; Groff, Shannon L.; Bultz, Barry D.; Carlson, Linda E.
Abstract Purpose Although research has indicated a diagnosis of cancer is most often distressing for patients and their families, few studies have examined which patients access resources to manage distress or how distress levels affect resource utilization. This study explored psychosocial and supportive care resource utilization in a large cancer population at a Canadian tertiary cancer centre over a 12‐month period in a usual care setting. Methods Patients who were new to the Tom Baker Cancer Centre completed the Distress Thermometer, the Pain and Fatigue Thermometers, the Psychological Screen for Cancer (Part C) that measures anxiety and depression, self‐report questions on resources accessed and a demographic form at baseline, 3, 6 and 12 months. No feedback or specific triage to services was provided in order to observe usual care practices. Results A total of 714 patients provided baseline data with 505 retained at 12 months. Twenty‐four percent indicated they accessed at least one service (e.g. individual counselling, nutritionist or resource social worker) over the 12 months. Patients who were older, less educated and with lower income were less likely to access services. People who reported higher symptom burden were more likely to access services at each time point. Conclusions Overall levels of access of psychosocial services were relatively low in this population and varied by socio‐demographic variables and symptom burden. Routine monitoring of psychosocial, practical and physical concerns is a potential strategy for targeting individuals who may require additional information or support in accessing available services to manage their concerns. Copyright © 2011 John Wiley & Sons, Ltd.